Simple preparation method of high-performance film composite forward osmosis membrane

By using ultra-large pore size base film and surfactant modification methods, the problems of different concentration polarization and low water flux in TFC-FO films were solved, and the preparation of high-performance films was achieved, which significantly improved the application potential in the field of water treatment.

CN119548986APending Publication Date: 2025-03-04JIANGNAN UNIV +1

Patent Information

Application Number
CN202411632363.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-15
Publication Date
2025-03-04

AI Technical Summary

Technical Problem

The existing modification methods cannot effectively solve the problem of concentration polarization caused by the TFC-FO membrane structure and the low water flux. It requires a simple, economical and can significantly improve the water flux.

Method used

A base film with an ultra-large pore size is used as a support layer, and a surfactant is introduced into the aqueous solution. By reducing the surface tension of the aqueous phase, the polyamide generation and the water transport area are promoted, and the high-performance TFC-FO film is finally synthesized through interfacial polymerization.

Benefits of technology

The water flux and retention performance of the TFC-FO membrane are significantly improved. The FO performance is further improved with the increase of the pore size of the support layer, greatly improving the application potential of the membrane in the field of water treatment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119548986A_ABST
    Figure CN119548986A_ABST
Patent Text Reader

Abstract

The invention discloses a simple preparation method of a high-performance film composite forward osmosis membrane, and belongs to the technical field of water treatment. The preparation method comprises the following steps: firstly, selecting a basement membrane with an ultra-large aperture as a supporting layer of the TFC to relieve a concentration polarization phenomenon and provide a larger interface specific surface area for the growth of polyamide; then, a surfactant is introduced into the water-phase solution to further promote the improvement of the effective water delivery area of the membrane. And finally, carrying out interfacial polymerization reaction on the surface of the substrate membrane to synthesize the TFC-FO membrane with higher performance. The TFC-FO membrane prepared through the method has excellent water flux and interception performance, the FO performance of the TFC-FO membrane is continuously improved along with increase of the pore diameter of the supporting layer, and the application potential of the TFC-FO membrane in the technical field of water treatment is greatly improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a simple preparation method of a high-performance thin-film composite forward osmosis membrane, belonging to the technical field of water treatment. Background Art

[0002] At present, ecological environment destruction and water shortage have seriously hindered the development of human society. In order to cope with this problem, various water treatment technologies have been rapidly developed. Forward osmosis (FO) is a new membrane separation technology that uses the osmotic pressure difference of the solution on both sides of the membrane as the driving force. Due to its advantages such as low energy consumption, high recovery rate, high rejection rate and light membrane pollution, FO has attracted widespread attention and is widely used in many fields such as seawater desalination, wastewater treatment, food processing and power generation. Thin film composite forward osmosis membrane (TFC-FO membrane), as the most used FO membrane, is mainly composed of a porous support layer and a dense selective layer generated by interfacial polymerization reaction. It has excellent solute separation ability and environmental tolerance. Moreover, FO technology does not require external pressure and consumes almost no energy during operation, so it has great application prospects in the future. However, the overall performance of TFC-FO membrane is still limited by factors such as concentration polarization, water transmission distance and water transmission area, which seriously restricts the application and development of TFC-FO membrane.

[0003] Concentration polarization is a phenomenon in which the relative diffusion of solvent and solute forms solute accumulation or transitional dilution on the membrane surface, which causes the actual osmotic pressure difference on both sides of the membrane to be much smaller than the theoretical calculated value, thereby reducing the water flux. For FO technology that relies on osmotic pressure difference as a driving force, concentration polarization is an important factor limiting the water flux level.

[0004] In existing applications, TFC-FO membranes mostly use ultrafiltration membranes with a pore size of 0.22μm as the base layer. Although the pore size has been greatly increased compared to the base membranes of nanofiltration and reverse osmosis TFC membranes, there is still a serious concentration polarization in practical applications, and the water flux is far lower than the theoretical value. By regulating the structural parameters of the TFC-FO membrane support layer, such as increasing the pore size and porosity, the concentration polarization phenomenon can be effectively alleviated. However, current research generally believes that as the pore size of the base membrane increases, the meniscus-shaped interface structure in the interfacial polymerization method will increase, and the larger the meniscus structure, the more polyamide internal permeation will occur, which will increase the water transmission resistance. Therefore, at this stage, research on the use of ultra-large membrane pore base membranes to synthesize high-performance TFC-FO membranes has not yet appeared.

[0005] Although modifying the base membrane can optimize the permeability of the TFC membrane, there are also some problems. For example, expensive materials are usually used to lay the middle layer, which is not only economical but also reduces the stability of the membrane. For example, in CN111068519B, amphiphilic macromolecules / metal nanoparticles are fixed on the base membrane. Although the improvement effect is relatively good, the metal nanoparticles used include gold nanoparticles and silver nanoparticles, which are expensive. This technology is not suitable for promotion and utilization.

[0006] Some of the disclosed modification methods have complicated steps and the water flux improvement is not high. For example, CN 107789994A provides a forward osmosis separation membrane composed of a polysulfone support layer and a polyamide active layer, but its water flux is only 8.57 to 15.69 L×m -2 h -1 , the salt reverse flux is only 2.11~3.29g×m -2 h -1 . Summary of the invention

[0007] [Technical issues]

[0008] The existing modification methods cannot effectively solve the concentration polarization phenomenon and low water flux problems caused by the TFC-FO membrane structure. Therefore, it is necessary to provide a method that is simple to prepare, economical and has a good water flux improvement effect.

[0009] [Technical solution]

[0010] In order to solve the above problems, the present invention first selects a substrate membrane with an ultra-large pore size as the support layer of the TFC-FO membrane to alleviate the concentration polarization phenomenon and create a larger meniscus reaction interface. After that, a surfactant is further introduced into the aqueous solution to promote the formation of polyamide and increase the water transmission area by reducing the surface tension of the aqueous phase. Finally, a TFC-FO membrane with high performance is synthesized by interfacial polymerization on the surface of the substrate membrane. The high-performance TFC-FO membrane prepared by the present invention has excellent water flux and interception performance, and its FO performance can be further continuously improved as the pore size of the support layer increases, which greatly enhances the application potential of the TFC-FO membrane in the field of water treatment technology.

[0011] The first object of the present invention is to provide a method for preparing a high-performance TFC-FO membrane, comprising the following steps:

[0012] (1) Modification of aqueous solution during TFC membrane interfacial polymerization:

[0013] Dissolving a surfactant and m-phenylenediamine in water to form an aqueous phase solution;

[0014] (2) Preparation of high-performance TFC-FO membrane:

[0015] The substrate membrane is immersed in the aqueous solution obtained in step (1), the substrate membrane is taken out and dried, and then immersed in a trimesoyl chloride solution to perform an interfacial polymerization reaction. Finally, after the interfacial polymerization reaction is completed, the substrate membrane is taken out and subjected to a thermal cross-linking reaction to finally obtain a high-performance TFC-FO membrane.

[0016] In one embodiment of the present invention, the surfactant in step (1) includes anionic, neutral ionic and cationic surfactants.

[0017] In one embodiment of the present invention, the surfactant in step (1) is an anionic surfactant.

[0018] In one embodiment of the present invention, the surfactant in step (1) comprises sodium dodecylbenzene sulfonate (SDBS) or sodium dodecyl sulfate (SDS).

[0019] In one embodiment of the present invention, the concentration of the surfactant in the aqueous solution in step (1) is 0.25 to 3 times the critical micelle concentration (CMC) of the surfactant; preferably, the concentration is 0.25 to 1.0 times the critical micelle concentration of the surfactant.

[0020] More preferably, the concentration of the surfactant in the aqueous solution in step (1) is 0.25 to 0.5 times the critical micelle concentration of the surfactant.

[0021] The critical micelle concentration refers to the minimum concentration at which surfactant molecules associate to form micelles in a solution; when the surfactant concentration reaches CMC, the surface tension of the solution drops to the minimum value. At this time, if the concentration is increased further, the surface tension of the solution will no longer decrease, but a large number of micelles will be formed.

[0022] Specifically, optionally, the concentration of the surfactant in the aqueous solution in step (1) is 0.3 to 0.6 mM / L.

[0023] In one embodiment of the present invention, the mass fraction of the intermediate phenylenediamine in the aqueous solution in step (1) is 0.1-5%.

[0024] In one embodiment of the present invention, the average pore size of the surface of the substrate membrane in step (2) is 1.00 to 5.00 μm.

[0025] In one embodiment of the present invention, the average pore size of the surface of the basement membrane in step (2) is 1.00-2.00 μm.

[0026] In one embodiment of the present invention, the immersion time in step (2) is 1 to 10 minutes, and the immersion temperature is 15 to 25°C.

[0027] In one embodiment of the present invention, the solvent of the benzene trimesoyl chloride solution in step (2) is a non-polar organic solvent; the non-polar organic solvent includes n-hexane or n-heptane.

[0028] In one embodiment of the present invention, the mass fraction of trimesoyl chloride in the trimesoyl chloride solution in step (2) is 0.01-0.5%.

[0029] In one embodiment of the present invention, the time of the interfacial polymerization reaction in step (2) is 1 to 10 minutes, and the temperature of the interfacial polymerization reaction is 15 to 25°C.

[0030] In one embodiment of the present invention, the thermal crosslinking reaction in step (2) is carried out in a water bath or air bath atmosphere; the temperature of the thermal crosslinking reaction is 40 to 100° C., and the time of the thermal crosslinking reaction is 1 to 20 minutes.

[0031] A second object of the present invention is to provide a high performance TFC-FO membrane according to the above method.

[0032] The third object of the present invention is to apply the high-performance TFC-FO membrane provided by the present invention in the fields of seawater desalination, water treatment and food processing.

[0033] A fourth object of the present invention is to provide a water treatment device, wherein the core membrane assembly of the water treatment device is equipped with the high-performance TFC-FO membrane.

[0034] [Beneficial Effects]

[0035] (1) The ultra-large pore basement membrane selected in the present invention has a larger meniscus interface, allowing higher amine monomer release and larger polyamide growth area, and the larger free space can reduce the obstruction to the transmission of solute and solvent molecules, thereby reducing the concentration polarization phenomenon; and the surfactant selected in the present invention can significantly reduce the surface tension of the aqueous solution, reduce the cross-boundary transmission resistance of the monomer and promote the generation of nanobubbles, making the surface of the polyamide layer more wrinkled, increasing the osmotic pressure difference and the effective water transmission area, so that the permeability performance of the TFC-FO membrane continues to increase; in addition, the surfactant can also reduce the structural defects of the polyamide layer and improve the solute retention capacity.

[0036] (2) Compared with the technology of laying the middle layer and modifying the structural properties of the support layer, the process of the present invention is simpler and can be completed in only two steps; the cost is low, and there is no need to use multiple reagents and the amount of reagents used is small; the effect is significant, and the water flux is 20L×m -2 h -1Moreover, the FO performance of the prepared high-performance TFC-FO membrane can be continuously improved as the pore size of the support layer increases, thereby effectively improving the competitive advantage of the FO membrane in the field of water treatment. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] Figure 1 Schematic diagram of the method for preparing high-performance TFC-FO membrane.

[0038] Figure 2 The reverse salt flux and water flux data of the TFC-FO membranes prepared in Examples 1 to 3 and Comparative Examples 1 to 9 are shown in FIG.

[0039] Figure 3 Graph showing the ratio of reverse salt flux to water flux of the TFC-FO membranes prepared in Examples 1 to 3 and Comparative Examples 1 to 9.

[0040] Figure 4 The reverse salt flux and water flux data of the TFC-FO membrane prepared in Comparative Examples 1, 2, 3 and Comparative Examples 10 to 18 are shown in FIG.

[0041] Figure 5 Graph showing the ratio of reverse salt flux to water flux of the TFC-FO membranes prepared in Comparative Examples 1, 2, 6 and Comparative Examples 10 to 18. DETAILED DESCRIPTION

[0042] The preferred embodiments of the present invention are described below. It should be understood that the embodiments are for better explaining the present invention and are not used to limit the present invention.

[0043] Test Method

[0044] 1. Water flux:

[0045] The mass of the drawn liquid on one side is continuously recorded by an automatic counting balance. The water flux can be obtained according to the change in the mass of the drawn liquid before and after the operation according to formula (1):

[0046]

[0047] In formula (1), J W Indicates the water flux of the membrane, L·m -2 ·h -1 ; ΔV represents the volume of raw liquid permeating the membrane, L; Δt represents the time of the test experiment, h; A m Represents the effective area of ​​the membrane, m 2 .

[0048] 2. Reverse salt flux:

[0049] By testing the conductivity of the raw liquid before and after operation, its ion concentration can be calculated. According to the volume change of the raw liquid before and after operation, the reverse salt flux can be obtained using formula (2):

[0050]

[0051] In formula (2), J s is the reverse salt flux of the membrane, g·m -2 ·h -1 ; C0 and C t are the initial and final salt concentrations of the raw material solution, mg·L -1 ; V0 and V t are the volumes of the raw material solution at the beginning and end, L; Δt represents the experimental time, h; A m Represents the effective area of ​​the membrane, m 2 .

[0052] Raw materials used in the examples

[0053] The support layer was a polyethersulfone (PES) substrate membrane with an average surface pore size of 1.00 μm and a diameter of 47 mm, both purchased from Haining Yibo Filter Equipment Factory, China;

[0054] The reagents or instruments used without indicating the manufacturer are all conventional products that can be purchased from the market;

[0055] If no specific technology or conditions are specified, they shall be carried out in accordance with the common knowledge in the field or the product instructions.

[0056] Example 1

[0057] A simple preparation method of a high-performance thin film composite forward osmosis membrane comprises the following steps:

[0058] (1) Modification of aqueous solution during interfacial polymerization of thin film composite membranes:

[0059] The anionic surfactant sodium dodecylbenzene sulfonate (SDBS) was dissolved in water and ultrasonically vibrated to make it dissolve evenly to form a 0.30mM / L sodium dodecylbenzene sulfonate aqueous solution (the critical micelle concentration of SDBS is 1.2mM / L). Then, metaphenylenediamine (MPD) was added to the aqueous solution to obtain an MPD aqueous phase solution, wherein the amount of MPD added was 3.4% of the total mass of the aqueous phase solution.

[0060] (2) Preparation of high-performance thin film composite forward osmosis membrane:

[0061] First, a polyethersulfone-based membrane with an average pore size of 1.00 μm was placed on a glass plate and fixed with a circular polytetrafluoroethylene plate frame with an inner diameter of 4 cm, a rubber pad and a clamp. 6.70 mL of MPD aqueous solution was poured on the membrane surface, soaked at 25 ° C for 2 minutes, then the aqueous solution was poured out, and the excess solution on the membrane surface was quickly removed using a rubber roller. Then 7.33 mL of TMC / n-hexane solution with a mass fraction of 0.15% was poured on the membrane surface and reacted at 25 ° C for 1 minute. The reacted membrane was then drained for 1 minute and transferred to a 98 ° C water bath for 2 minutes for thermal cross-linking. After the reaction, a high-performance TFC-FO membrane was obtained, named TFC-l-0.30mM.

[0062] Example 2

[0063] The concentration of sodium dodecylbenzenesulfonate in the aqueous solution in step (1) of Example 1 was adjusted to 0.60 mM / L; the other conditions were kept consistent with Example 1 to obtain a high-performance TFC-FO membrane named TFC-1-0.60 mM.

[0064] Example 3

[0065] The concentration of sodium dodecylbenzenesulfonate in the aqueous solution in step (1) of Example 1 was adjusted to 1.20 mM / L; the other conditions were kept consistent with Example 1 to obtain a high-performance TFC-FO membrane named TFC-1-1.20 mM.

[0066] Comparative Example 1

[0067] A method for preparing a conventional TFC-FO membrane comprises the following steps:

[0068] First, a polyethersulfone-based membrane with an average pore size of 1.00 μm was placed on a glass plate and fixed with a circular polytetrafluoroethylene frame with an inner diameter of 4 cm, a rubber pad and a clamp. 6.70 mL of a 3.4% MPD aqueous solution (without adding surfactant) was poured on the membrane surface, soaked at 20°C for 2 minutes, then the aqueous solution was poured out, and the excess solution on the membrane surface was quickly removed using a rubber roller. Then 7.33 mL of a 0.15% TMC / n-hexane solution was poured onto the membrane surface and reacted at 20°C for 1 minute. After that, the reacted membrane was drained for 1 minute and transferred to a 98°C water bath for 2 minutes for thermal crosslinking. After the reaction, a conventional TFC-FO membrane was obtained, which was named TFC-l-Control.

[0069] Comparative Example 2

[0070] The average surface pore size of the substrate membrane in Comparative Example 1 was adjusted to 0.45 μm, and the other parameters were kept consistent with Comparative Example 1 to obtain a conventional TFC-FO membrane, which was named TFC-m-Control.

[0071] Comparative Example 3

[0072] The average surface pore size of the substrate membrane in Comparative Example 1 was adjusted to 0.22 μm, and the other parameters were kept consistent with Comparative Example 1 to obtain a conventional TFC-FO membrane, which was named TFC-s-Control.

[0073] Comparative Example 4

[0074] The average surface pore size of the substrate membrane in step (2) of Example 1 was adjusted to 0.45 μm, and the rest was kept consistent with Example 1 to obtain a surfactant-modified TFC-FO membrane named TFC-m-0.30 mM.

[0075] Comparative Example 5

[0076] The average surface pore size of the substrate membrane in Example 2 was adjusted to 0.45 μm, and the other parameters were kept the same as in Example 2 to obtain a surfactant-modified TFC-FO membrane named TFC-m-0.60 mM.

[0077] Comparative Example 6

[0078] The average surface pore size of the substrate membrane in Example 3 was adjusted to 0.45 μm, and the other parts were kept consistent with Example 3 to obtain a surfactant-modified TFC-FO membrane named TFC-m-1.20 mM.

[0079] Comparative Example 7

[0080] The average surface pore size of the substrate membrane in step (2) of Example 1 was adjusted to 0.22 μm, and the rest was kept consistent with Example 1 to obtain a surfactant-modified TFC-FO membrane named TFC-s-0.30 mM.

[0081] Comparative Example 8

[0082] The average surface pore size of the substrate membrane in Example 2 was adjusted to 0.22 μm, and the other parameters were kept the same as in Example 2 to obtain a surfactant-modified TFC-FO membrane named TFC-s-0.60 mM.

[0083] Comparative Example 9

[0084] The average surface pore size of the substrate membrane in Example 3 was adjusted to 0.22 μm, and the other parameters were kept the same as in Example 3 to obtain a surfactant-modified TFC-FO membrane named TFC-s-1.20 mM.

[0085] Comparative Example 10

[0086] The anionic surfactant sodium dodecylbenzene sulfonate (SDBS) in step (1) of Example 1 was replaced by a cationic surfactant cetyltrimethylammonium bromide (CTAB) (the critical micelle concentration of CTAB is 0.92 mM / L), and the added concentration of the surfactant was adjusted to 0.23 mM / L. Other conditions were consistent with Example 1 to obtain a surfactant-modified TFC-FO membrane, named TFC-1-0.23 mM.

[0087] Comparative Example 11

[0088] The anionic surfactant sodium dodecylbenzenesulfonate in step (1) of Example 1 was replaced by the cationic surfactant hexadecyltrimethylammonium bromide, and the added concentration of the surfactant was adjusted to 0.46 mM / L. The other conditions were the same as those of Example 1, and a surfactant-modified TFC-FO membrane was obtained, named TFC-1-0.46 mM.

[0089] Comparative Example 12

[0090] The anionic surfactant sodium dodecylbenzenesulfonate in step (1) of Example 1 was replaced by the cationic surfactant hexadecyltrimethylammonium bromide, and the concentration of the surfactant was adjusted to 0.92 mM / L. The other conditions were the same as those of Example 1 to obtain a surfactant-modified TFC-FO membrane named TFC-1-0.92 mM.

[0091] Comparative Example 13

[0092] The anionic surfactant sodium dodecylbenzene sulfonate in step (1) of Example 1 was replaced with the cationic surfactant hexadecyltrimethylammonium bromide, and the concentration of the surfactant was adjusted to 0.23 mM / L. In addition, the average pore size of the substrate membrane in step (2) was adjusted to 0.45 μm, and the rest was the same as in Example 1, to obtain a surfactant-modified TFC-FO membrane named TFC-m-0.23 mM.

[0093] Comparative Example 14

[0094] The anionic surfactant sodium dodecylbenzene sulfonate in step (1) of Example 1 was replaced with the cationic surfactant hexadecyltrimethylammonium bromide, and the concentration of the surfactant was adjusted to 0.46 mM / L. In addition, the average pore size of the substrate membrane in step (2) was adjusted to 0.45 μm, and the rest was the same as in Example 1, to obtain a surfactant-modified TFC-FO membrane named TFC-m-0.46 mM.

[0095] Comparative Example 15

[0096] The anionic surfactant sodium dodecylbenzene sulfonate in step (1) of Example 1 was replaced with the cationic surfactant hexadecyltrimethylammonium bromide, and the concentration of the surfactant was adjusted to 0.92 mM / L. In addition, the average pore size of the substrate membrane in step (2) was adjusted to 0.45 μm, and the rest was the same as in Example 1, to obtain a surfactant-modified TFC-FO membrane named TFC-m-0.92 mM.

[0097] Comparative Example 16

[0098] The anionic surfactant sodium dodecylbenzene sulfonate in step (1) of Example 1 was replaced with the cationic surfactant hexadecyltrimethylammonium bromide, and the concentration of the surfactant was adjusted to 0.23 mM / L. In addition, the average pore size of the substrate membrane in step (2) was adjusted to 0.22 μm, and the rest was the same as in Example 1, to obtain a surfactant-modified TFC-FO membrane named TFC-s-0.23 mM.

[0099] Comparative Example 17

[0100] The anionic surfactant sodium dodecylbenzene sulfonate in step (1) of Example 1 was replaced with the cationic surfactant hexadecyltrimethylammonium bromide, and the concentration of the surfactant was adjusted to 0.46 mM / L. In addition, the average pore size of the substrate membrane in step (2) was adjusted to 0.22 μm, and the rest was the same as in Example 1, to obtain a surfactant-modified TFC-FO membrane named TFC-s-0.46 mM.

[0101] Comparative Example 18

[0102] The anionic surfactant sodium dodecylbenzene sulfonate in step (1) of Example 1 was replaced with the cationic surfactant hexadecyltrimethylammonium bromide, and the concentration of the surfactant was adjusted to 0.92 mM / L. In addition, the average pore size of the substrate membrane in step (2) was adjusted to 0.22 μm, and the rest was the same as in Example 1, to obtain a surfactant-modified TFC-FO membrane named TFC-s-0.92 mM.

[0103] The forward osmosis membranes of Examples 1-3 and Comparative Examples 1-18 were placed in a laboratory-made forward osmosis membrane reactor (disclosed in the literature Zhao, Pin et al. "Explore the forward osmosis performance using hydrolyzed polyacrylamide as draw solute for dye wastewater reclamation in the long-term process." Chemical Engineering Journal 273 (2015): 316-324.) for performance testing. The test results are shown in FIG. Figure 2 shown.

[0104] from Figure 2 It can be seen that the weakening of concentration polarization makes the TFC-l-Control membrane have a higher water flux and equivalent reverse salt flux than the TFC-s-Control and TFC-m-Control membranes, but the amount of improvement is not large. It is speculated that the large pore size of the base membrane aggravates the internal penetration of polyamide, which in turn increases the water transmission resistance.

[0105] Figure 2 and Figure 3 It is shown that after the anionic surfactant SDBS is introduced into the water phase, the water flux of TFC-1-0.30mM is greatly improved, which is significantly higher than that of TFC-s-1.20mM and TFC-m-1.20mM, and the reverse salt flux and specific salt flux (the ratio of reverse salt flux to water flux) continue to decrease. This shows that by greatly increasing the pore size of the basement membrane, the infiltrated polyamide layer can be centrally split to form a concave polyamide morphology with a high specific surface area, and the release of amine monomers can be effectively increased to promote the formation of a highly wrinkled polyamide layer. Therefore, synthesizing a polyamide layer on a large-pore basement membrane is an effective strategy to improve the performance of the TFC-FO membrane. However, after increasing the amount of SDBS, the increase in the water flux and specific salt flux of the TFC-1 membrane is already low, indicating that it is close to the limit of improvement.

[0106] Figure 4 and 5It is shown that after the cationic surfactant CTAB is introduced into the water phase, the water flux, reverse salt flux and specific salt flux of all membranes are greatly reduced, indicating that the cationic surfactant CTAB is not suitable for the modification of the base membrane system of the present invention. However, it should be pointed out that surfactants of different ionic types do not actually have obvious advantages and disadvantages, but they show different effects in different membrane systems. For example, in the TFC-FO membrane system of the present invention, the comprehensive effect of the anionic SDBS is better, but in the TFC-NF membrane, the cationic surfactant CTAB can also show an effect comparable to that of the anionic surfactant. Therefore, the selection of surfactants for thin-film composite forward osmosis membranes still requires experimental testing and data analysis.

[0107] In summary, although different ionic surfactants will reduce the specific salt flux and improve the membrane quality, the anionic surfactant has a more significant effect on the improvement of water transmission area and water flux, and the specific salt flux is relatively lower under the same conditions. Combined with time efficiency, anionic surfactants are the most optimized choice in this method. And because the subsequent improvement effect of TFC-1 membrane is limited, by combining economic investment, TFC-1-0.30mM with a small amount of SDBS has the most optimized comprehensive effect. In general, adding a small amount of anionic surfactants on the ultra-large pore support layer to promote the growth of the effective area of ​​the membrane surface can easily produce a high-performance TFC-FO membrane.

[0108] Although the present invention has been disclosed as above in the form of a preferred embodiment, it is not intended to limit the present invention. Anyone familiar with this technology can make various changes and modifications without departing from the spirit and scope of the present invention. Therefore, the scope of protection of the present invention should be based on the definition of the claims.

Claims

1. A method for preparing a high-performance TFC-FO membrane, characterized in that: The steps include: (1) Modification of aqueous solution during TFC membrane interfacial polymerization: Dissolving a surfactant and m-phenylenediamine in water to form an aqueous phase solution; (2) Preparation of high-performance TFC-FO membrane: The substrate membrane is immersed in the aqueous solution obtained in step (1), the substrate membrane is taken out and dried, and then the substrate membrane is immersed in a trimesoyl chloride solution to perform an interfacial polymerization reaction, and finally the substrate membrane is taken out after the interfacial polymerization reaction is completed and then subjected to a thermal crosslinking reaction, so as to finally obtain a high-performance TFC-FO membrane; The surfactant in step (1) is an anionic surfactant; the concentration of the surfactant in the aqueous solution in step (1) is 0.25 to 1.0 times the critical micelle concentration of the surfactant; The average pore size of the surface of the basement membrane in step (2) is 1.00 to 5.00 μm.

2. The preparation method according to claim 1, characterized in that: The surfactant in step (1) includes sodium dodecylbenzene sulfonate or sodium dodecyl sulfate.

3. The preparation method according to claim 1, characterized in that: The mass fraction of phenylenediamine in the aqueous solution in step (1) is 0.1-5%.

4. The preparation method according to claim 1, characterized in that: The average pore size of the surface of the basement membrane in step (2) is 1.00 to 2.00 μm.

5. The preparation method according to claim 1, characterized in that: The immersion time in step (2) is 1 to 10 minutes, and the immersion temperature is 15 to 25°C.

6. The preparation method according to claim 1, characterized in that: In step (2), the solvent of the benzyl chloride solution is a non-polar organic solvent; and the mass fraction of the benzyl chloride in the benzyl chloride solution is 0.01-0.5%.

7. The preparation method according to claim 1, characterized in that: In step (2), the interfacial polymerization reaction time is 1 to 10 minutes, and the temperature of the interfacial polymerization reaction is 15 to 25° C.; the thermal crosslinking reaction is carried out in a water bath or air bath atmosphere; the temperature of the thermal crosslinking reaction is 40 to 100° C., and the thermal crosslinking reaction time is 1 to 20 minutes.

8. A high performance TFC-FO membrane, characterized in that: The high-performance TFC-FO membrane is prepared according to the preparation method described in any one of claims 1 to 7.

9. Application of the high performance TFC-FO membrane described in claim 8 in the fields of seawater desalination, water treatment and food processing.

10. A water treatment device, characterized in that: The core membrane module of the water treatment device is equipped with the high-performance TFC-FO membrane described in claim 8.

Citation Information

Patent Citations

  • Forward osmosis separation membrane and preparation method thereof

    CN107789994A

  • A forward osmosis membrane and its preparation method

    CN111068519B

  • Forward osmosis composite membrane based on large-aperture base membrane, and production method thereof

    CN108295667A

Cited By

  • A simple preparation method of high-performance thin film composite forward osmosis membrane

    CN122806319A